Reflections on the possible codification of European private international law - González Beilfuss, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The paper analyses a possible codification of European private international law on the basis of its incompleteness. Four types of gaps are identified and it is found that incompleteness is a structural feature and not a transitory situation, which leads to the exploration of a renewed version of a “code” in order to improve access to law by rationalising and systematising the sources.
Keywords: European private international law; codification; gaps; role of private international law; alternatives for the rationalisation and systematisation of sources